Healthmaking in Ancient Egypt : The Social Determinants of Health at Deir el-Medina - Austin, Anne E., (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2024., 2024)
This book explores the health of ancient Egyptians living in the New Kingdom village of Deir el-Medina. Through an interdisciplinary approach that combines skeletal analysis with textual evidence, the book examines how social factors, such as social support, healthcare access, and economic stability, played crucial roles in buffering individuals from stress and promoting good health. This is the first, comprehensive book on the bioarchaeology of Deir el-Medina including data from human remains spanning the site's New Kingdom occupation. This book highlights how the Social Determinants of Health can be used to explain how past people maintained their health.